Performance approximations and bounds for non‐real‐time traffic in an integrated service system. Issue 1 (1st March 2014) - Huang, Yue‐Cai; Ko, King‐Tim; Zukerman, Moshe
Abstract : The authors consider an integrated service system, where real‐time (RT) calls of multiple rate requirements and non‐real‐time (NRT) calls share the total system capacity. Typically, RT calls are given strict priority over NRT calls; therefore NRT performance is dependent on the RT process. When RT call arrivals do not follow a Poisson process, the effect of the RT traffic burstiness on the NRT performance has not been investigated. In this study, the authors investigate this effect and provide computationally efficient approximations and bounds for the NRT performance evaluation in the integrated service system with multi‐rate non‐Poisson RT traffic. With known first and second moments of the RT call arrival processes, the authors propose to consider the multi‐rate non‐Poisson RT traffic streams as an equivalent single‐rate Poisson traffic stream. Then, the authors evaluate the NRT performance by converting the original system to a system offered with the equivalent RT traffic and the NRT traffic. The authors' approximations and bounds are validated by extensive numerical examples.